(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Meniscal tears are the second most common knee injuries which may lead to chronic pain, reduced mobility, and a higher risk of osteoarthritis if untreated. It may be correlated with Bhagna in ayurveda. Sushrutacharya, in Bhagna chikitsa, recommends Bandhana and Snehaseka for Janu Bhagna, followed by rehabilitative exercises. Methodology: This study aimed to compare the efficacy of a selected Ayurvedic protocol with a standard treatment protocol in MRI-confirmed meniscal injuries. 24 participants were randomly divided into two groups of 12 in each group and treated for 35 days at VPSV Ayurveda College, Kottakkal. Assessments were done on Day 0 and Day 35, with a follow-up after one month. Both groups received Bandhana for 3 weeks. The study group underwent Shashtika Taila Seka and exercises, while the control group received Dhanwantara Taila seka, Shashtika Pinda Sveda, and Matravasti for 2 weeks. Internal medications such as Dhanwantara Kashaya, Lakshaguggulu Vati, and Gandha Taila were given to both groups. Results: Statistical analysis showed improvement in both groups, with the study group showing slightly better symptom relief. The mean difference between the study and control groups was tested for non-inferiority using one-sided t-test and study group was found to be non-inferior. Conclusion: The selected Ayurvedic protocol was found non-inferior to the standard Ayurvedic protocol in managing meniscal tears and improving quality of life.